PROFESSIONAL TRAINING OF ELECTRONICS ENGINEERS: APPLYING US EXPERICENCE TO UKRAINAN HIGHER EDUCATION INSTITUTIONS - Pavlenko Olha (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article discusses the current state of professional training of engineers, in particular, electronics engineers in Ukrainian higher education institutions (HEIs) and explores best practices from US HEIs. The research outlines the features of professional training of electronics engineers and recent changes in Ukrainian HEIs. Such challenges for Ukrainian HEIs as lack of collaboration between higher education and science with industry, R&D cost reduction for HEIs, and downsizing the research and academic staff, the disparity between the available quality of human capital training and the demanded are addressed. The study attempts to identify successful practices of US HEIs professional training of engineers in order to suggest potential improvements in education, research, and innovation for training electronics engineers in Ukraine